Synthesis of zeolite from rice husk ash and kaolinite clay for the removal of methylene blue from aqueous solution - Justice Hayfron; Sirpa Jääskeläinen; Samuel Tetteh (Heliyon)
Zeolite was successfully synthesized using a mixture of kaolinite clay (which served as the alumina source) and rice husk ash (silica source). The aim of this work was to synthesize highly efficient zelolite to remove methyle blue dye from aqueous solution. The synthesized adsorbent was characterised using Fourier Transform Infrared (FTIR) spectroscopy, powder x-ray diffraction (PXRD) analysis, differential scanning calorimetry (DSC), thermogravimetric analysis (TGA) and pH at the point of zero charge (pHpzc). The interaction of the zeolite with methylene blue was studied using equilibrium batch process. Factors investigated include; solution pH, adsorbent dose, ionic strength, adsorption temperature and initial dye concentration. Results show removal efficiencies between 80 and 90 %. Assessment of adsorption isotherms using the Freundlich and Langmuir models showed that the data from this work fitted the Freundich model with Kf = 7.388 mg1-1/nL1/ng−1 and n = 0.89 signifying a physisorption model. The data also fitted the pseudo-second-order kinetic models with R2 = 1.00. Assemment of the thermodynamic parameters gave an enthalpy change (ΔH°) of −1.871 kJ/mol and an entropy change (ΔS°) of +10.18 JK−1mol−1. Generally the Gibbs free energy (ΔG°) was negative and dereased with temperature. Results from this study shows that zeolite prepared from readily available raw materials is an efficient adsorbent for the removal of methylene blue from aqueous solution.